Functional expression and secretion of basic fibroblast growth factor in Lactococcus lactis - Ho, Pooi Leng; Chua, Yu Feng; Quek, Jun Ping; Ng, Say Kong; Wong, Fong Tian; Ow, Dave Siak-Wei (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCultivated meat, produced by in vitro cell culture in bioreactors, offers a sustainable alternative to traditional meat sources. A significant challenge in its production is the high cost of mitogenic growth factors, which are essential supplements in serum-free media for cultivating meat cells. One strategy to reduce cost involves minimizing purification cost by using a food-grade host to secrete growth factors. In this study, we investigate the production of recombinant FGF2 (Fibroblast Growth Factor 2) through secretion in Lactococcus lactis, a Generally Recognized As Safe (GRAS) organism.MethodTo enhance the secretion in L. lactis, we employed the USP45 secretory peptide and secretion propeptide (PP1) in the design of our recombinant FGF2-G3. Optimization was performed on various culture parameters that influence protein expression, including media formulation, nisin concentration, induction timing, temperature, and culture duration. Secreted FGF2-G3 produced under optimized conditions was purified and tested for bioactivity on Anguilla japonica pre-adipocytic cells, Aj1C-2x.Results and DiscussionWe have generated a recombinant L. lactis strain and an optimal expression strategy to enable the production of secreted bioactive growth factors. Our results demonstrate that this system can produce FGF2 which were able to promote the proliferation of fish Anguilla japonica pre-adipocytic cells. Despite minimal purification beyond affinity purification and buffer exchange, we were able to obtain comparable specific activity to commercial FGF2. The final yields can be derived at 1.97 mg/L and through simple protein purification and buffer exchange. Finally, this study highlights the potential use of L. lactis secretion as an endotoxin-free alternative, compared to E. coli, for production of growth factors for use in cultivated meat production.